A study on shaping tourists’ conservational intentions towards cultural heritage in the digital era: exploring the effects of authenticity, cultural experience, and place attachment - Junjie Li; Xiangbin Peng; Xiaodong Liu; Huanchen Tang; Wei Li (Journal of Asian Architecture and Building Engineering)
With the rapid development of digital tourism, more and more tourists are embracing this innovative mode of tourism. Digital tourism has attracted a large influx of tourists, which not only promotes the dissemination of local culture, but also promotes tourists’ intention to preserve culture. This study proposes a comprehensive framework authenticity, cultural experience, place attachment, satisfaction, and cultural protection intention, aiming to explore tourists’ cultural protection intention in digital tourism. To validate our framework, we use the Digital Intelligence Niushou as a case study and distributed a questionnaire to tourists, obtaining 408 valid responses. We analyzed the collected data using structural equation modeling (SEM). The results showed that place attachment and the four cultural experiences positively influenced both visitors’ satisfaction and cultural protection intention. Notably, “scientific knowledge” and “personal values” emerged as the biggest influences on cultural protection intention. Among the three types of authenticity, only objective authenticity and constructed authenticity positively influenced tourists’ satisfaction and cultural protection intention. This suggests that faithfully restored historical contexts play a key role in shaping tourists’ experiences and attitudes toward cultural protection in the field of digital tourism. This study provides a solid theoretical foundation for advancing digital tourism and enhancing tourists’ commitment to preserving cultural heritage. Our findings are important for digital tourism platforms to develop more effective optimization strategies, and can help managers to create more attractive, authentic and immersive tourism models to enhance tourist satisfaction and cultivate cultural protection intention.